2019
DOI: 10.1073/pnas.1903228116
|View full text |Cite
|
Sign up to set email alerts
|

High-speed AFM reveals subsecond dynamics of cardiac thin filaments upon Ca 2+ activation and heavy meromyosin binding

Abstract: High-speed atomic force microscopy (HS-AFM) can be used to study dynamic processes with real-time imaging of molecules within 1- to 5-nm spatial resolution. In the current study, we evaluated the 3-state model of activation of cardiac thin filaments (cTFs) isolated as a complex and deposited on a mica-supported lipid bilayer. We studied this complex for dynamic conformational changes 1) at low and high [Ca2+] (pCa 9.0 and 4.5), and 2) upon myosin binding to the cTF in the nucleotide-free state or in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 54 publications
6
27
0
Order By: Relevance
“…A). The usefulness of this lipid bilayer has been demonstrated in Hs‐AFM studies on the interactions between actin filaments and several actin‐binding proteins . First, we visualized actin filaments and confirmed that they were right‐handed double‐helical filaments (Fig.…”
Section: Resultssupporting
confidence: 58%
“…A). The usefulness of this lipid bilayer has been demonstrated in Hs‐AFM studies on the interactions between actin filaments and several actin‐binding proteins . First, we visualized actin filaments and confirmed that they were right‐handed double‐helical filaments (Fig.…”
Section: Resultssupporting
confidence: 58%
“…When [Ca 2+ ] i is increased, Ca 2+ -bound TnC interacts with TnI, and the carboxyl-terminal domain of TnI is dissociated from actin. The Tn conformational changes result in displacement of Tm on actin, which subsequently induces myosin binding to actin and force generation (e.g., Haselgrove, 1973;Huxley, 1973;Lehman et al, 1994;Vibert et al, 1997;Xu et al, 1999;Fukuda et al, 2009;Risi et al, 2017;Matusovsky et al, 2019). It has been reported that during the shift of the thin filament state from "off " to "on, " strongly bound myosin cooperatively enhances binding of neighboring myosin molecules that have ATP and thereby potentially produce force (Greene and Eisenberg, 1980;Trybus and Taylor, 1980).…”
Section: Ca 2+ -Dependent Activation Of Thin Filamentsmentioning
confidence: 99%
“…Yu et al [ 260 ] applied the high-speed atomic force microscope with ultra-short cantilevers to unfold the individual bacteriorhodopsin molecules in a native lipid bilayer. Matusovsky and co-workers [ 261 ] studied the 3-state model of activation of cardiac thin filaments isolated as a complex and deposited on a mica-supported lipid bilayer. They realized that the successful imaging of the regulatory proteins tropomyosin and troponin complexes is dependent on the force applied by the cantilever tip because of their low affinity to F-actin.…”
Section: High-speed Imagingmentioning
confidence: 99%